One-Phase Smart Switch using OpenCV Hand Gesture Recognition - Fauzan, Mochamad Rizal; Khairi, Saiqa Fatur; Kaniarudi, Neneng Puspita; Ath Thahirah Al Azhima, Silmi; Arief Hakim, Nurul Fahmi; Kustiawan, Iwan; Al Qibtya, Mariya; Elvyanti, Siscka (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2024)
The need for simplicity in various activities encourages further technological development. One of them is a system to turn lights on and off with just a hand gesture. This hand gesture-based One-phase smart switch uses OpenCV, Arduino Nano, relays, and webcam cameras to recognize hand gestures. Static finger movements are used as buttons to turn on the lights. The results show that the algorithm used has high reliability with a precision score of 0.90, sensitivity of 0.90, accuracy of 0.96, and F1-score of 0.90. The accuracy of the system is affected by light intensity, distance, and hand tilt angle. At a light intensity of 70 LUX, the accuracy reaches 100%, while at 40 LUX the accuracy ranges from 98-99%. A distance of 30-60 cm gave the best accuracy of 100%, but decreased at longer distances. A hand tilt of 0° gives 100% accuracy, while at an angle of 60° the accuracy drops significantly, especially for the fifth finger with 64% accuracy. The average response time of the light to finger movement is 0.133 seconds. This device can recognize a variety of finger patterns well, thus meeting the desired needs.